The semantics of the structural elements in Tuvan dance - Sanchay, Choygan Kh.; Kukhta, Maria S. (The New Research of Tuva, 2019)
The article presents an analysis of the dance gestures and the geometry of dance as ritual and ceremonial heritage of Tuvans. Dance is understood as an integral cultural phenomenon with its own rituals and ceremonial, as well as motions, posture and gestures related to household, employment, games etc. All of these are filled with ethnic and cultural meanings and associated with a specific ethnocultural identity. The structural-semantic approach makes it possible to analyze dance as a language expressed by the semantics of its gestures. The study’s source base includes published works on traditional ceremonies of Tuvans and peoples of related ethnic culture; and also materials of field studies conducted in Mongolia among ethnic Tuvans in 2018. Kinetic traditions of Tuvan dance can be said to "remember" and "preserve" mythological subjects. The Tep traditional Tuvan dance features trampling movements akin to those made by sacred animals (deer, mountain goats, etc.). The rite of syg kezherde yөreёl contains dance moves with feet making geometric shapes on the ground. The dance figure of circular rotations has links with the solar cult, and the semantics of the legs — with the totem kinesics. The Devig ritual dance – also known as the "dance of the eagle" - features interesting hand gestures. Swinging their hands like flapping birds’ wings, wrestlers thank Tengri, the creator deity of the sky. Touching the ground with the hand is an expression of deep respect to mother earth. The tradition of circular movements and circular composition appears in the Tuvan dance of Cheler-Oi.